Pengaruh Wabah Covid-19 Terhadap Omzet Penjualan Konveksi Pakaian: Prespektif Ekonomi Syari’ah - Furqon Nur Islamiati; Nurnasrina Nurnasrina (LPMP Imperium, 2021)
study aims to determine how much influence the Covid-19 outbreak has on the turnover of clothing convection sales in Pekanbaru City. The research data was collected from clothing convection entrepreneurs in maintaining their business in the pandemic era and how the Islamic economy reviews the efforts of clothing convection entrepreneurs in maintaining their business in the pandemic era. The results showed an effect of the Covid 19 outbreak on the sales turnover of clothing convection. As for the sharia economic review regarding the efforts used by clothing convection entrepreneurs, follow the sharia concept because they have optimism and leave the nature of breaking up and are willing to work hard to innovate products tailored to consumer needs. So that the convection business they run continues to survive even in the pandemic era.